Determinants Affecting the Liquidity of Commercial Banks in Vietnam: A Longitudinal Analysis - Minh, Ngo Ngoc; Thuc, Nguyen Ngoc; Quang, Bui Van (International Journal of Psychosocial Rehabilitation, 2020)
The paper uses fixed effect model (FEM) to study the factors affecting the liquidity ratio of 34 Vietnamese commercial banks in the period 2005-2019. The empirical results show that the bank size, the ratio of equity to total capital, credit risk, the ratio of loans to total assets, the growth rate of gross domestic product variables negatively effect on liquidity ratio while the return on equity variable positively impacts on the liquidity ratio of commercial banks. On that basis, the paper proposes some policy recommendations to better manage liquidity, creating one of the prerequisites for a sustainable economic development in the long term.